Molecular Weight Effect on the Absorption, Charge Carrier Mobility, and Photovoltaic Performance of an Indacenodiselenophene-Based Ladder-Type Polymer - Intemann, Jeremy J; Yao, Kai; Yip, Hin-Lap; Xu, Yun-Xiang; Li, Yong-Xi; Liang, Po-Wei; Ding, Fei-Zhi; Li, Xiaosong; Jen, Alex K.-Y (Chemistry of materials, 2013)
Selenium substitution on a ladder-type indacenodithiophene-based polymer (PIDT-DFBT) is investigated in order to reduce band gap, improve charge mobilities, and enhance the photovoltaic performance of the material. The new indacenodiselenophene-based polymer (PIDSe-DFBT) possessed improved absorption over its sulfur analogue in films, as well as substantially higher charge mobilities (0.15 and 0.064 cm2/(V s) hole and electron mobility, respectively, compared to 0.002 and 0.008 cm2/(V s) for PIDT-DFBT). The enhanced material properties led to an improved power conversion efficiency of 6.8% in photovoltaic cells, a 13% improvement over PIDT-DFBT-based devices. Furthermore, we examined the effect of molecular weight on the properties of PIDSe-DFBT and found not only a strong molecular weight dependence on mobilities, but also on the absorptivity of polymer films, with each 15 000 g/mol increase in weight, leading to a 25% increase in the absorptivity of the material. The molecular weight dependence of the material’s properties resulted in a significant difference in photovoltaic performance with the high-molecular-weight PIDSe-DFBT providing a higher photocurrent, fill factor, and efficiency due to its improved absorption and hole mobility. These results demonstrate the importance of achieving high molecular weight and the potential that selenium-containing ladder-type polymers have in the design of high-performance semiconducting polymers for organic photovoltaics (OPVs).